Relevansi Teori Fraud Hexagon dalam Mendeteksi Fraudulent Financial Statement Pada Perusahaan Sektor Perbankan - Selvi Fouziah; Suratno Suratno; Syahril Djaddang (SUBSTANSI, 2022)
This research aims to analyze the relevance  of fraud hexagon theory against  fraudulent financial statement. The population in this study was all banks listed on the Indonesia Stock Exchange (IDX) in 2015-2019. While the sample in this study as many as 28 companies and 100 units of analysis taken based on purposive sampling techniques. The study used multiple linear regression methods with the SPSS 25 analysis tool. The results showed that the relevant factors in detecting fraud in financial statements consisted of financial stability, managerial ownership, and state owned entreprise. While other factors consisting of external pressure, nature of industry, ineffective monitoring, TATA, and CEO Education are irrelevant in detecting the possibility of fraud in banking financial statements.